Development of Guide Basic Life Support (BLS) Application Based on Android to Increase Accuracy Compression Ritme And Ventilation to Handling of Out Hospital Cardiac Arrest - Candra Adi Wirawan; Sandi Alfa Wiga Arsa (Babali Nursing Research, 2020)
Introduction: Public health center as first-rate health facilities must be equipped with basic emergency services capability to support optimal health service systems. The ability of nurses in doing a heart massage or BLS is still below 50%. In the management of BLS, increasing the ability of nursing was important to reduce mortality due to cardiac arrest. The purpose of this research was to know the effect of Basic Life Support (BLS) based guide application in handling Out Cardiac arrest (OHCA) Nurse emergency departments Public health center. Methods: This research used the R & D method. Data of stage 1 was collected through a questionnaire of knowledge, attitude and Psychomotor BLS from 50 nurses for application development in stage 2, then conducted trials and evaluation. Phase 2 was conducted by a quasi-experiment method with a simple random sampling technique with 25 respondents in each group. The control group was given the BLS module and the treatment group was given Guide Basic Life Support (BLS) application for 2 weeks. The variables in phase 2 of were the accuracy and speed of resuscitation, measured by a checklist and stopwatch. Results: The result of the research was an application of basic life support (BLS) based on Android. The result for the treatment group showed the precision variable (p = 0,000) and speed (p = 0,000) for the Wilcoxon Test and the precision variable (p = 0,000) and speed (p = 0,000) for Mann U Whitney Test. Conclusion: Basic android basic life support (BLS) application can improve the accuracy and speed of nurses in doing BLS.